Exploring the Dimensionality of a Brief School Readiness Screener for Use With Latino/a Children. (June 2014) - Quirk, Matthew; Rebelez, Jennica; Furlong, Michael
This study contributed to the school readiness literature by examining the factor structure and reliability of a revised version of the Kindergarten Student Entrance Profile (KSEP). Teachers rated 579 Latino/a children during the first month of kindergarten using the KSEP. Factor analysis procedures (exploratory factor analysis [EFA] and confirmatory factor analysis [CFA]) supported a two-factor solution, social-emotional (SE; α = .88), cognitive (COG; α = .81), factor loadings > .51. These results provide evidence supporting the interpretation of KSEP ratings as distinct measures of Latino/a children's SE and COG readiness at the time of kindergarten entry. Additional implications of the findings are also discussed.